Determinants of economic activity - the keynesian perspective - Bludnik, Izabela (Uniwersytet Ekonomiczny we Wrocławiu, 2008)
The lack of effective demand is commonly treated as a cornerstone of Keynesian attitude towards the deterioration of economic activity and a drop in growth indexes. However, the Keynesian paradigm has been evolving for seventy years. Hence, the opinions concerning the causes of downturn should expose the same tendency. Actually, John M. Keynes and post-war Keynesians ascribed the economic problems to the demand side of market. Together with the development of Keynesianism the demand started to lose its meaning. Step by step it became a second-order factor influencing the economy only temporarily. It is the supply side that plays a much more important role nowadays. New Keynesians claim that in order to attain suitable growth indexes (high employment above all) one must remove the barriers and imperfections typical of supply side. Thus, identifying the term “Keynesian policy” with “demand policy” became ungrounded and misleading
Argumenta Oeconomica, 2008, No 1 (20), s. 19-30
Keywords: Keynesianism; economic growth; demand side; supply side